Carbon emissions reduction effects of sustainable development policy in resource-based cities from the perspective of resource dependence: Theory and Chinese experience. (September 2022) - Zheng, Heyun; Ge, Liming
Abstract: Once prosperous resource-based cities are gradually falling into decline as the intensity of resource extraction and utilization continuously increases. Recently proposed targets of carbon peak by 2030 and carbon neutrality by 2060 have pushed, emission-reduction and eco-economic sustainability of these cities to the forefront. Accordingly, this study considers China's Sustainable Development Plan of National Resource-based Cities, 2013–2020 (SDP) as a quasi-natural experiment. The impacts of the SDP on carbon emissions and correlated effects under different changes in resource dependence are explored. Further analyses are aimed at differentiating SDP effects from the perspectives of region, financial autonomy, and investment in science and technology, as well as SDP's spatial spillover effects on resource-dependence. Results show SDP has a significant dampening effect on carbon emissions in resource-based cities. Moreover, as resource dependency increases, the reduction effects become more obvious, as evidenced by growing and mature cities. The effects are strongest in the south-east region of Heihe-Tengchong Line and cities with higher financial autonomy and investment in science and technology. Ultimately, as the degree of resource dependence increases, the SDP has the significant spatial spillover effect. This study provides a novel perspective and serves as a useful reference for achieving carbon neutrality for resource-based cities in China. Highlights: Carbon neutrality targets require substantial further reductions across all sectors. The China's Sustainable Development Plan of National Resource-based Cities (SDP) significantly reduces the carbon emissions. As resource dependence increases, the SDP significantly decreases emissions. The impact of SDP on carbon emissions differs for resource-based cities at different stages of development. The SDP's effects on carbon emissions are spatially heterogeneous.